2021
DOI: 10.1016/j.jbc.2021.100308
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of Myxococcus xanthus MglC, a component of the polarity control system, and its interactions with its paralog MglB

Abstract: The δ-proteobacteria Myxococcus xanthus displays social (S) and adventurous (A) motilities, which require pole-to-pole reversal of the motility regulator proteins. M utual gl iding motility protein C (MglC), a paralog of GTPase-activating protein M utual gl iding motility protein B (MglB), is a member of the polarity module involved in regulating motil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 72 publications
4
22
0
Order By: Relevance
“…A structural model of the RomR/MglC/MglB complex To gain structural insights into the RomR/MglC/MglB complex, we used structural information, our functional data and AlphaFold-Multimer structural predictions to model this complex. The AlphaFold-Multimer models of the MglB dimer and MglC dimer were predicted with high confidence and agreed well with the crystallographic structures 35,40,41 (Fig. S7ABC), documenting the validity of the structural predictions.…”
Section: A) Because This Region Is Apart From the Fdi Region And Mglc...supporting
confidence: 64%
See 4 more Smart Citations
“…A structural model of the RomR/MglC/MglB complex To gain structural insights into the RomR/MglC/MglB complex, we used structural information, our functional data and AlphaFold-Multimer structural predictions to model this complex. The AlphaFold-Multimer models of the MglB dimer and MglC dimer were predicted with high confidence and agreed well with the crystallographic structures 35,40,41 (Fig. S7ABC), documenting the validity of the structural predictions.…”
Section: A) Because This Region Is Apart From the Fdi Region And Mglc...supporting
confidence: 64%
“…The MglC homodimer's structure is similar to that of MglB with two-helix and four-helix sides (Fig. 4A) 35 . Based on conservation, McLoon et al reported the MglC F25A D26A I28A variant (henceforth MglC FDI ) with substitutions on the two-helix side (Fig.…”
Section: The Mglc Fdi Surface Region Represents the Interface For Int...mentioning
confidence: 74%
See 3 more Smart Citations